IMPLEMENTASI PROGRAM E-SAMSAT DALAM RANGKA MENINGKATKAN DAN MENYEDERHANAKAN PELAYANAN MASYARAKAT DI KANTOR UPT BAPENDA SIDOARJO - Kurniawan, Bagus Ananda; Ismail, Ismail; Alverdo, Marchelino Joshua (Jurnal Sosial Humaniora Sigli, 2023)
This study aims to describe the implementation of the e-Samsat program in order to improve and simplify community services at the UPT Bappenda Sidoarjo office in supporting public services that are transparent in tax sector revenue. This study used a qualitative research method with a descriptive research type. The location of this research includes government institutions that have involvement with the implementation of E-Samsat, namely the Regional Revenue Agency of Sidoarjo Regency as the agency in charge of implementing it. Data collection techniques were carried out by in-depth interviews with informants, activity documentation, and the use of written documents. Furthermore, the data analysis technique is by means of data reduction, data presentation, and drawing conclusions. Through the results of research conducted by researchers using an implementation indicator from Edward III with a communication indicator that has gone well through a series of socialization processes and dissemination through social media and print media. Indicators of disposition/attitude, the staff is good enough in providing services to taxpayers. In the indicator the organizational structure has been going well with the governor's regulations governing tax payments using the online system. On the resource dimension, training was held to improve the quality of the performance of staff at the Sidoarjo Regency Regional Revenue Agency.Key Words: implementation, e-samsat, tax